Research on the properties of ferronickel production slags and development of technological schemes for their enrichment - Shevchenko , D.V.; Ovcharuk , A.M.; Nadtochii , A.A.; Prikhodko , S.V.; Shutov , V.Yu. (Theory and Practice of Metallurgy, 2025)
Objective. Determination of the physicochemical properties of slags, phase composition, and forms of nickel presence in them, development of enrichment modes and equipment parameters. Research Methods and Equipment. X-ray spectral microanalysis (RSMA) on the SELMI REM-106I installation was used to determine the distribution of nickel between the metallic and oxide phases in the presented slag samples. Dry and wet gravity and magnetic separation using modernized magnetic separators established the possibility of slag enrichment and the distribution of nickel between the enrichment products. Research Results. This work has conducted research on the gravitational-magnetic separation of electro-furnace and refining slags of ferronickel production in the conditions of the Pobuzhsky ferronickel plant. The efficiency of implementing the developed technological schemes in production was shown, providing additional extraction in the amount of 119 tons or 9.8% of the total annual nickel production at the plant. Slag samples were ground in experimental ball mills to fractions of –0.16; 0.16¸1.6 and +1.6 mm and subjected to enrichment by gravity and magnetic separators with a magnetic induction on the drum surface of 0.3-0.6 T (Tesla) of the MBS-300 and MS-500 types with a total metal phase yield of up to 30%. Scientific Novelty. RSMA established that nickel, both in electric furnace granulated slags and in refining slags, is in the metallic phase and is represented by metal nuggets in combination with iron of various shapes and sizes. Enrichment of electric furnace and refining slags by a combined method using a high-intensity magnetic field will allow obtaining a metal concentrate containing 0.9-38% nickel. The combined enrichment method using high-intensity magnetic separators is one of the most promising for enriching both primary mineral raw materials and secondary materials of ferrous and non-ferrous metal production. Practical Significance. The developed and proposed for implementation technological schemes for enrichment of electric furnace slags using the “wet” technology and refining slags using the “dry” technology allow for the utilization of about 1200 tons of nickel per year or the extraction of 31.6% and 94.65% of nickel from slags, respectively.